Medicinal plants species used in male circumcision among the Bagishu of Eastern Uganda: Medicinal plants used in circumcision - Anywar, Godwin Upoki; Nakitende, Gloria (Ethnobotany Research and Applications, 2022)
Background: Plants have long been used in traditional medicine and in cultural practices such as circumcision. Circumcision is one of the oldest and most widely performed procedures globally. Although male circumcision among the Bagishu in Eastern Uganda has been widely studied, these studies have focused on social and cultural aspects of the ritual. No study has ever investigated the medicinal plant species used during the process despite their widespread use and importance. Methods: An ethnobotanical study was conducted in Sironko district, in Eastern Uganda, to document the medicinal plants used by the Bagishu during the male circumcision ritual. Semi-structured questionnaires were used for data collection. Fifteen traditional practitioners were identified using the snowball technique and interviewed. Results: Four medicinal plant were used in male circumcision, namely: Cissampelos mucronata A.Rich, Conyza sumatrensis (S.F.Blake) Pruski & G.Sancho, Dracaena fragrans (L.) Ker Gawl, and Urtica massaica Mildbr. These herbs are either administered orally or applied topically on wounds. C. mucronata was the most frequently used plant for wound healing. It is also believed to give courage and embolden young men before circumcision. Conclusion: The Bagishu use medicinal plants during circumcision rituals mainly for treating wounds and stopping bleeding. This knowledge is on the verge of being lost despite its potential economic and health benefits in terms of wound healing. Key words: Traditional practitioners, male circumcision, medicinal plants, Uganda